Biological Variation of Plasma and Urinary Markers of Acute Kidney Injury in Patients with Chronic Kidney Disease. (6th January 2020) - Carter, Joanne L; Parker, Christopher T; Stevens, Paul E; Eaglestone, Gillian; Knight, Sarah; Farmer, Christopher K T; Lamb, Edmund J
Abstract: BACKGROUND: Identification of acute kidney injury (AKI) is predominantly based on changes in plasma creatinine concentration, an insensitive marker. Alternative biomarkers have been proposed. The reference change value (RCV), the point at which biomarker change can be inferred to have occurred with statistical certainty, provides an objective assessment of change in serial tests results in an individual. METHODS: In 80 patients with chronic kidney disease, weekly measurements of blood and urinary biomarker concentrations were undertaken over 6 weeks. Variability was determined and compared before and after adjustment for urinary creatinine and across subgroups stratified by level of kidney function, proteinuria, and presence or absence of diabetes. RESULTS: RCVs were determined for whole blood, plasma, and urinary neutrophil gelatinase-associated lipocalin (111%, 59%, and 693%, respectively), plasma cystatin C (14%), creatinine (17%), and urinary kidney injury molecule 1 (497%), tissue inhibitor of metalloproteinases 2 (454%), N -acetyl-β-d -glucosaminidase (361%), interleukin-18 (819%), albumin (430%), and α1 -microglobulin (216%). Blood biomarkers exhibited lower variability than urinary biomarkers. Generally, adjusting urinary biomarker concentrations for creatinine reduced ( P < 0.05) within-subject biological variability (CVI ). For some markers, variation differed ( P < 0.05) between subgroups. CONCLUSIONS: These data can form a basis for application of these tests in clinical practice and research studies and are applicable across different levels of kidney function and proteinuria and in the presence or absence of diabetes. Most of the studied biomarkers have relatively high CVI (noise) but also have reported large concentration changes in response to renal insult (signal); thus progressive change should be detectable (high signal-to-noise ratio) when baseline data are available.